Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics